RELATIONSHIPS AMONG GENES FOR COMMERCIALLY VALUABLE TRAITS IN C. ANNUUM VAR. ANNUUM L.: PATTERN CONSTRUCTION AND ANALYSIS - O. O. Timina (Вавиловский журнал генетики и селекции)
Summarized data are presented to identify coordinated chains of commercially valuable characters (CVCs) and the corresponding alleles. A conceptual diagram of their relationships based on ecological and genetic identification of 16 CVCs in C. annuum var. annuum is shown. The structure of the complex of informative allele effects associated with heterosis for the marketable yield character has been refined by multivariate statistics.